Ornithologic: A Structural Analysis of Dutch Bird Nomenclature - van den Broek, Gerard J. (Anthropologica, 2022)
As a departure from tradition this article analyses a Western system of classification: Dutch bird taxonomy. It would appear that the difference between "cold" and "warm" societies is less extensive than one might think. In Western societies a difference exists between some kinds of classification. There are the so-called "scientific" classifications, which are inspired by Aristotle's work, and there are the folk taxonomies, which are collective representations and which, consequently, have no individual creator. This difference appears most plainly if one speaks of a priori and a posteriori classifications. Dutch bird taxonomy is of the latter type; one could, following Locke, describe it as a series of natural kind as opposed to nominal kind terms. The principles upon which the taxonomy is constructed are examined in some detail.